Effects of Epitaxial Strain on Antiferrodistortion of AgNbO3 from First‐Principle Calculations. Issue 4 (21st February 2018) - Zhu, Linguang; Wang, Xiangjian; Lou, Xiaojie
Abstract : Using the first‐principles approaches, we obtain a phase diagram of AgNbO3 as a function of in‐plane epitaxial strain, and two phase transitions (from Pm to Cm and from Cm to Amm2) were found throughout the whole range of strain. In particular, our study shows that the antiferrodistortion (AFD) is misfit‐dependent. Our results indicate that compressive in‐plane lattice strain can enhance the AFD instability of AgNbO3, which originates from the stronger coupling between the out‐of‐plane lattice strain and AFD than coupling with in‐plane lattice strain. In order to overcome the overestimation of rotational angle caused by the underestimation of lattice parameters, we construct a Gibbs free energy under a certain external pressure to obtain a reasonable angle, which is about 8.39°. We expect our results may offer some insights for designing and fabricating AgNbO3 thin films with excellent antiferroelectric properties by using compressive strain engineering. Abstract : In this letter, structural phase transition induced by epitaxial strain in AgNbO3 is studied using first‐principles calculations. It is found that the antiferrodistortion is misfit‐dependent. The antiferrodistortion instability can be enhanced by in‐plane lattice strain. The excellent antiferroelectric properties can be obtained by using compressive strain engineering.